salmon: A Symbolic Linear Regression Package for Python - Alex Boyd; Dennis L. Sun (Journal of Statistical Software)
One of the most attractive features of R is its linear modeling capabilities. We describe a Python package, salmon, that brings the best of R's linear modeling functionality to Python in a Pythonic way - by providing composable objects for specifying and fitting linear models. This object-oriented design also enables other features that enhance easeof-use, such as automatic visualizations and intelligent model building.